2020
DOI: 10.1186/s13054-020-03117-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hydroxychloroquine, lopinavir/ritonavir, and standard of care in critically ill patients with SARS-CoV-2 pneumonia: an opportunistic retrospective analysis

Abstract: Background: The severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) outbreak is spreading worldwide. To date, no specific treatment has convincingly demonstrated its efficacy. Hydroxychloroquine and lopinavir/ ritonavir have potential interest, but virological and clinical data are scarce, especially in critically ill patients. Methods: The present report took the opportunity of compassionate use and successive drug shortages to compare the effects of two therapeutic options, lopinavir/ritonavir and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 24 publications
1
56
0
1
Order By: Relevance
“…Ten articles from Medrxiv/Google Scholar were added, so 29 articles were included, of which 25 were observational studies, one was an interventional non-randomized study and three were RCT. These studies included 27 articles for hydroxychloroquine [ [14] , [15] , [16] , [17] , [18] , [19] , 23 , 24 , 36 , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] ] and 12 articles for hydroxychloroquine + azithromycin [ 18 , 36 , 41 , 42 , 47 , 48 , 50 , 51 , [57] , [58] , [59] , [60] ]. For chloroquine, after searching PubMed, Cochrane Review, Embase and Web of Science, 449 articles were identified.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten articles from Medrxiv/Google Scholar were added, so 29 articles were included, of which 25 were observational studies, one was an interventional non-randomized study and three were RCT. These studies included 27 articles for hydroxychloroquine [ [14] , [15] , [16] , [17] , [18] , [19] , 23 , 24 , 36 , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] ] and 12 articles for hydroxychloroquine + azithromycin [ 18 , 36 , 41 , 42 , 47 , 48 , 50 , 51 , [57] , [58] , [59] , [60] ]. For chloroquine, after searching PubMed, Cochrane Review, Embase and Web of Science, 449 articles were identified.…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies were conducted in the USA [ 15 , 18 , 23 , 41 , 42 , 49 , 50 , 53 , 56 , 58 ], four in Spain [ 16 , 17 , 44 , 57 ], seven in France [ 13 , 24 , 46 , 48 , 54 , 59 , 60 ], one in the UK [ 40 ], two in Italy [ 43 , 65 ], one in China [ 14 ], one in Brazil [ 51 ] and three in several other countries (USA, Canada, Italy and Spain) [ 39 , 47 , 52 ]. Twenty-two articles were published [ [13] , [14] , [15] , 17 , 18 , 24 , 39 , 41 , 43 , 44 , 46 , 47 , [49] , [50] , [51] , [52] , [53] , [54] , 56 , 57 , 59 , 60 , 65 ] and six articles were preprints [ 16 , 23 , 40 , 42 , 48 , 58 ]. Mean daily dose of hydroxychloroquine ranged from 333 mg/day to 945 mg/day.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding indicates that the use of hydroxychloroquine at this stage of disease would be not useful. Randomized controlled trials are required to show whether this drug could be useful in ICU patients admitted for Covid-19 [15] .…”
Section: Discussionmentioning
confidence: 99%
“…A case study of a patient, treated with Lopinavir/Ritonavir for chronic HIV demonstrate that the treatment failed not only to prevent SARS-CoV-2 infection, but also failed to prevent rapid progression to severe pneumonia [85]. Also a retrospective study did not confirm the efficacy of Lopinavir/Ritonavir in COVID19 treatment compared to standard care [100]. Also the comparison of effectiveness of Lopinavir/Ritonavir to Arbidol demonstrate the superiority of Arbidol in COVID-19 treatment [203].…”
Section: Viral Protease Inhibitors Lopinavir/ritonavir (Kaletra Aluvia)mentioning
confidence: 98%